INFLUENCE OF YALTIAN PROTOCOLS ON SOVIET-TURKISH RELATIONS - Dervish, Leyla; Devrisheva, Halida (Journal of history, 2018)
The article examines the influence of decisions taken during the Yalta International Conference of the anti-Hitler coalition on the nature of bilateral Soviet-Turkish relations. At the same time, the foreign policy of the Turkish Republic is characterized, and its influence on the strategy of the Soviet government, which took an ultimatum form during the Second World War is analyzed. The author notes the fallacy of the position of the USSR towards Turkey and its exceptionally negative influence on the possibility of realizing the strategic interests of the USSR in the region.